The Influence of Music Activities on Children’s Creative Thinking Development - Liu, Yulin (SHS web of conferences, 2023)
Nowadays, all countries in the world regard creativity as one of the core abilities of talent competition. The core of cultivating creative talents is to carry out creative education. Early childhood is the enlightenment period of creative education. During this period, children have not formed a set of thinking, protecting and stimulating their imagination, curiosity and desire to explore. Because music education plays a unique role in fostering children’s creativity, it is beneficial to the development of children’s creative thinking and the formation of creative personality. The purpose of this article is to analyse and study the characteristics of children’s early thinking development, innovative music teaching concepts and teaching methods, and to develop children’s action thinking, image thinking, abstract thinking and creative thinking at this stage through innovative rhythmic activities and Orff teaching, focusing on the specific period of children. It can promote their brain more active and more comprehensive. Through the research, it is found that the professional quality and innovation of preschool teachers play an important role in the development of children’s creative thinking, and rhythmic activities and Orff music teaching method are suitable for the development of children’s creative thinking, and have a larger space for exploration.